Influence of Drying-Wetting Cycles on Dynamic Tensile Properties of Red-Sandstone Using the Brazilian Test - Bin Du; Wu Sun; Qiangqiang Cheng (Advances in Materials Science and Engineering)
The phenomenon of the drying-wetting cycle is a component of the weathering process and has a significant impact on the characteristics of rock materials. In order to examine the physical and dynamic tensile properties of red sandstone subjected to drying-wetting cycles, physical tests and dynamic splitting tensile tests were performed on red sandstone specimens under varying drying-wetting conditions. First, the split Hopkins pressure bar was used to perform dynamic tensile tests on red sandstone samples after varying numbers of drying-wetting cycles (0, 20, 40, 60, and 80). Second, the effects of the loading rate and drying-wetting cycles on dynamic tensile strength and energy dissipation of red sandstone were studied. Finally, taking into account the effect of the loading rate, a model was developed to predict the trend of decay in the dynamic tensile strength of red sandstone following drying-wetting cycles. The findings indicate that as the number of drying-wetting cycles increases, there is a decrease in longitudinal wave velocity and a marked degradation of the red sandstone due to the effects of the drying-wetting cycles. The dynamic tensile strength and dissipation energy density of red sandstone samples increase with the increasing loading rate. Under consistent loading rate conditions, the dynamic tensile strength and dissipative energy density of red sandstone samples exhibit a decrease as the number of drying-wetting cycles increases.